2019
DOI: 10.1177/0038026119868642
|View full text |Cite
|
Sign up to set email alerts
|

Place-by-proxy: Care infrastructures in a foundling room

Abstract: The concept of place has become fertile ground for sociological investigations, yet it is still undertheorized and in need of further development. Its most advanced employment is to be found within a sociological agenda on materialities of care and health architecture. In this article, we build on this work to conceptualize ‘placed care’ and to show how ecologies of care are produced and maintained through care infrastructures. The article investigates the case of an illegal baby foundling room in the Netherla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…They argue that individuals' domestic care possibilities are always ‘threaded through the housing system’ (Power & Mee, 2020, p. 500), which patterns tenant dynamics, promotes the market imaginary around home ownership, and legitimises ‘good’ and ‘acceptable’ housing‐mediated caring practices through various governing practices. Ivanova et al (2020), alternatively, use a baby foundling room in the Netherlands as an example to illustrate the emergence of new care infrastructure by tracing how the room temporarily aligns multiple established legal, media, political, information and health infrastructures beyond the room to enable essential caring for abandoned infants and abandoning mothers.…”
Section: Infrastructural Approach On Migration Care Relations and Urb...mentioning
confidence: 99%
“…They argue that individuals' domestic care possibilities are always ‘threaded through the housing system’ (Power & Mee, 2020, p. 500), which patterns tenant dynamics, promotes the market imaginary around home ownership, and legitimises ‘good’ and ‘acceptable’ housing‐mediated caring practices through various governing practices. Ivanova et al (2020), alternatively, use a baby foundling room in the Netherlands as an example to illustrate the emergence of new care infrastructure by tracing how the room temporarily aligns multiple established legal, media, political, information and health infrastructures beyond the room to enable essential caring for abandoned infants and abandoning mothers.…”
Section: Infrastructural Approach On Migration Care Relations and Urb...mentioning
confidence: 99%
“…Het concept liminaliteit is oorspronkelijk ontwikkeld door de Franse antropoloog Van Gennep (1960[1909) en wordt omschreven als 'a condition where the usual practice and order are suspended and replaced by new rites and rituals' (Czarniawska & Mazza, 2003, p. 267). Hoewel Van Gennep het concept in tijdelijke zin gebruikte, wordt liminaliteit in wetenschaps-en technologiestudies (STS) en organisatiestudies ook toegepast in ruimtelijke zin (Ellis & Ybema, 2010;Iedema et al, 2012;Short, 2015;Ivanova et al, 2020;Oldenhof et al, 2020;Rahmawan-Huizenga & Ivanova, 2022). In dit artikel conceptualiseren we stadslabs als een liminale ruimte om steden op alternatieve manieren te besturen.…”
Section: Stadslabs Als Een Liminale Ruimteunclassified
“…Likewise, researchers who study the re-placement of care as a means to govern health care have revealed the invisible work that goes into re-placing care and reflect on the political-symbolic use of places. This is nicely illustrated by Ivanova et al (2019), who describe an (illegal) private foundling room for infants that has never been used but offers the possibility of leaving an infant and, therefore, creates an infrastructure of care for both the mother (and/or father) and (unwanted) baby. This article highlights the 'infrastructural doings' the place engenders, such as a 24/7 helpline.…”
Section: Theoretical Frameworkmentioning
confidence: 99%